Effects of procrastination behavior, stress tolerance and study habits on academic achievements of Indian Students residing in India (Kerala) and UAE. - Smitha Dev (Research in Social Sciences and Technology, 2018)
This paper is designed to study various factors affecting the academic achievements of high school students. The study was conducted on 210 high school students from Abu Dhabi and Thiruvananthapuram. Procrastination behavior inventory, an index of stress tolerance and study habits scale were used to understand the various factors interfering their academic achievement. The data were analyzed using the statistical techniques; such as, Product-moment coefficient of correlation – person r, and factor analysis. Results provide an insight into the numerous factors effecting students in their learning process and it is a fact that students need to get adequate support and motivation from teachers and parents to keep up their focus on the educational goal.